Review of Global Research on E-Mobility: A Bibliometric Analysis - Desai, Apurvkumar; Patel, Chetan R. (Communications - Scientific Letters of the University of Zilina, 2023)
The present article portrays the bibliometric analysis of research conducted on E-mobility worldwide. The study aimed to understand research characteristics, evolution, challenges and potential research trends. Research articles published on E-mobility have been compiled from the Scopus database, resulting in 1737 articles published between 2001 and 2021. The software R Studio has been used for subsequent bibliometric analysis. The analysis examines the research trend in the field of E-mobility. In addition, it identifies the most productive contributors in terms of author, country and sources. Thematic analysis has been performed, as well, to reveal E-mobility research trends, including the most influential articles and authors. The study concludes that very few studies have been conducted on E-mobility and that there is much potential in E-mobility. The present paper can help the researcher pave the research path in E-mobility.
Keywords: e-mobility; EV; bibliometric analysis; research trend analysis; charging infrastructure; environment